Feasibility of interventions to increase HPV vaccination acceptability and coverage in school-based programs: Findings from a pilot study in Quebec, Canada - Maude Dionne; Chantal Sauvageau; Doriane Etienne; Holly O. Witteman; Ève Dubé (Preventive Medicine Reports)
Introduction: Human papillomavirus (HPV) vaccines have been offered in Quebec schools to 4th-grade (9–10 years old) girls since 2008 and boys since 2016. HPV vaccine coverage does not reach the 90 % target in many regions. This project evaluated the feasibility and the acceptability of interventions to improve HPV vaccine acceptability and coverage in school-based programs. Methods: The evaluation was conducted in 32 Quebec schools in 2019–2020. We tested a strategy of three interventions implemented in sequence (face-to-face information session, email reminder with an online decision support tool, and telephone reminder using motivational interviewing (MI) techniques). Parents and school staff completed online surveys. School nurses participated in individual interviews. Key stakeholders participated in a workshop to identify enabling conditions and barriers to implementing interventions across Quebec. Results: The strategy was generally well-received by school staff, nurses, and parents. Many parents found the 3 interventions helpful to support their vaccination decision. Most parents (92 %) suggested that the face-to-face information session and the decision support tool (82 %) be offered to all parents. Nevertheless, delivering classroom presentations was perceived by nurses as logistically challenging. Parents were generally satisfied with the telephone reminder, but only a limited number of nurses applied motivational interviewing techniques, as half (51 %) of unreturned consent forms were due to forgetfulness. Conclusion: Our strategy was accepted and deemed feasible by a majority of parents, school staff, and nurses. Collaboration between health authorities and schools is essential for implementing interventions to enhance vaccine acceptance in school-based programs.